Restorative Justice As An Alternative Form Of Criminal Case Resolution - Putri Indah Mubihanti (Fox Justi : Jurnal Ilmu Hukum, 2025)
This article aims to analyze the history, concept, and role of the restorative justice approach as an alternative solution in the context of crime and criminal justice. The analysis is conducted by examining historical and contemporary literature on restorative justice, crime, and criminal justice. The research method used in this article is juridical-normative legal research, where the focus is on written legal regulations or research based on prevailing rules or norms in societal life, aimed at uncovering a truth based on the logic of law from a normative perspective. This research also emphasizes the implementation practice with the legal practices.